Bicycling Infrastructure Design for Indian Cities and Emerging Economies - Pandit, Debapratim; Sharma, Deepa; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The book focuses on specific infrastructural solutions for bicycling for Indian cities and other emerging economies. It explores the current state of bicycling infrastructure in Indian cities and proposes standard and custom designs, guidelines, 2D and 3D illustrations, technical drawings as well as relevant discussions and explanations for the choice of right infrastructural solutions according to site constraints. This volume will be of great interest to those in academia and industry dedicated to a vision of creating inclusive streets in Indian cities and emerging economies to making the street safe and comfortable for bicyclists.
Introduction -- State of bicycling infrastructure in Indian cities -- Bicycle tracks -- Bicycle friendly intersections -- Bicycle parking facilities -- Signage.
Keywords: Transportation engineering; Traffic engineering; Sustainability; Engineering design; Construction industry Management.; Transportation Technology and Traffic Engineering; Sustainability; Engineering Design; Construction Management; Cycling -- India; Cycling -- Developing countries; Bicycle traffic flow -- India; Bicycle traffic flow -- Developing countries